CK17 and p16 expression patterns distinguish (atypical) immature squamous metaplasia from high-grade cervical intraepithelial neoplasia (CIN III) - Regauer, S (Blackwell Publishing Ltd, 2007)
Regauer S & Reich O (2007) Histopathology50, 629–635 CK17 and p16 expression patterns distinguish (atypical) immature squamous metaplasia from high-grade cervical intraepithelial neoplasia (CIN III) AIMS: Atypical immature metaplasia (AIM) refers to a full-thickness intraepithelial basaloid lesion in the uterine cervix that features both metaplasia and atypia and is therefore difficult to distinguish from high-grade cervical intraepithelial neoplasia (CIN III). p16 is a marker for human papillomavirus (HPV)-induced dysplasia. Cytokeratin (CK) 17 is a marker for cervical reserve (stem) cells, which give rise to metaplasia. The aim was to determine whether AIM can be reclassified into metaplasia and CIN III based on p16 and CK17 immunohistochemistry. MATERIAL AND RESULTS: Seventy-five cervical biopsy specimens, curettings and cone excisions containing varying proportions of dysplasia and metaplasia and 20 cases regarded as AIM were analysed immunohistochemically with antibodies to CK17, p16 and p63. In immature metaplasia all proliferating cells were immunoreactive with antibodies to CK17 and p63, while p16 was negative. All dysplastic cells of CIN III demonstrated uniform immunoreactivity for p16 and p63, but were CK17–. Based on the reciprocal immunoreactivity of p16 and CK17, 17/20 cases of AIM were reclassified as metaplasia (n = 10) and CIN III (n = 7). Three cases of AIM stained for both CK17 and p16 and were classified as CIN III. CONCLUSION: ‘AIM’ is a helpful histological descriptor but it should not be used as a final diagnosis. Immunohistochemistry for p16 and CK17 allows distinction between metaplasia and high-grade CIN.